Source region and growth analysis of narrowband Z‐mode emission at Saturn. Issue 12 (22nd December 2016) - Menietti, J. D.; Yoon, P. H.; Písa, D.; Ye, S.‐Y.; Santolík, O.; Arridge, C. S.; Gurnett, D. A.; Coates, A. J.
Abstract: Intense Z ‐mode emission is observed in the lower density region near the inner edge of the Enceladus torus at Saturn, where these waves may resonate with MeV electrons. The source mechanism of this emission, which is narrow‐banded and most intense near 5 kHz, is not well understood. We survey the Cassini Radio and Plasma Wave Science data to isolate several probable source regions near the inner edge of the Enceladus density torus. Electron phase space distributions are obtained from the Cassini Electron Spectrometer, part of the Cassini Plasma Spectrometer investigation. We perform a plasma wave growth analysis to conclude that an electron temperature anisotropy and possibly a weak loss cone can drive the Z mode as observed. Electrostatic electron acoustic waves and perhaps weak beam modes are also found to be unstable coincident with the Z mode. Quasi‐steady conditions near the Enceladus density torus may result in the observations of narrowband Z ‐mode emission at Saturn. Key Points: Source regions of Saturn 5 kHz Z ‐mode emission are located Wave amplitude and electron PSD are analyzed Temperature anisotropy and quasi‐steady conditions near Enceladus torus drive Z mode